Concepto de competencias en maestros del área de lengua castellana en Bogotá - Bernal Chávez, Julio Alexánder; Giraldo Aguirre, Greysi Milena (Enunciación, 2004)
The present document determines the incidence of the theory of lunguistics and communicative competences in the justifications presented by the teachers and researches of Spanish Language Arts classes with respect with their use in the educational context.As specific targets chosen we find to break down or analyze the theories that fundament and justify the concept of competence, to determine the recontextualization (second interweaving) that some researchers make with respect to the competences and identify the justifications of the teachers of Spanish language Arts classes and researchers of Spanish language about the competences.